The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1088/1674-1056/aba2e5
|View full text |Cite
|
Sign up to set email alerts
|

Plastic deformation mechanism transition of Ti/Ni nanolaminate with pre-existing crack: Molecular dynamics study*

Abstract: Tensile behaviors of Ti/Ni nanolaminate with model-I crack are investigated by molecular dynamics simulations. The Ti/Ni nanolaminates with center crack either in Ti layer or in Ni layer under different loading directions are utilized to systematically study the mechanical performance of the cracked material. The results indicate that pre-existing crack dramatically changes the plastic deformation mechanism of the Ti/Ni nanolaminate. Unlike the initial plastic deformation originating from the interface or weak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…In recent years, extensive research using MD simulations has been conducted to probe mechanical behaviors of nanoporous materials and the effect of voids. [17][18][19] Shang et al investigated the size-dependent effect of pre-void in the Ni/Ni 3 Al interface on tensile strength, and found that the small void disperses the local energy caused by lattice misfit at the interface, generating higher yield stress than the defect-free structure. [20] Guan et al simulated the dynamic response of Al containing spherical void under different loading patterns.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, extensive research using MD simulations has been conducted to probe mechanical behaviors of nanoporous materials and the effect of voids. [17][18][19] Shang et al investigated the size-dependent effect of pre-void in the Ni/Ni 3 Al interface on tensile strength, and found that the small void disperses the local energy caused by lattice misfit at the interface, generating higher yield stress than the defect-free structure. [20] Guan et al simulated the dynamic response of Al containing spherical void under different loading patterns.…”
Section: Introductionmentioning
confidence: 99%
“…For the case of isopachous Ti/Ni nanowires with larger layer thickness, the plastic behaviors are greatly different from those of previous two samples. The microstructure evolutions of the longest Ti/Ni MNW (λ = 7.17 nm) are presented in ior, which has also been discovered in simulation [21,22,[37][38][39] and experiment [40,41] of HCP materials. Hereafter, the newly formed Ti/Ni nanowire undergoes another elastic stage until the tensile strain reaches the 0.073.…”
Section: Atomic Configuration Evolutionsmentioning
confidence: 57%
“…After that, the FCC phase grows and occupies the entire Ti layer as a result of dense basal dislocations' propagation and accumulation of FCC stack faults. [37,38,42] And the specific orientational relationship of grain reorientation and the phase transformation have been described specifically in our previous work. [26] 096201-5 At the second strain rate, the plastic deformations are similar to those at ε = 1.0 × 10 8 s −1 , which contains the grain reorientation, allotropic phase transition and dislocations' movement in Ti layer, while Ni layer provides spring support in the tensile process.…”
Section: Atomic Configuration Evolutionsmentioning
confidence: 99%
“…[27] The common neighbor analysis (CNA) and dislocation extraction algorithm (DXA) are adopted to identify the atom feature and defect, where the grey means other atoms, the red represents HCP atoms, the blue expresses BCC atoms, the green suggests FCC atoms, and the lines in green regions indicate partial dislocations. [28,29] 3. Results and discussion…”
Section: Simulation Models and Methodsmentioning
confidence: 99%